2011
DOI: 10.1002/gcc.20928
|View full text |Cite
|
Sign up to set email alerts
|

Prostate stem cell antigen, a presumable organ‐dependent tumor suppressor gene, is down‐regulated in gallbladder carcinogenesis

Abstract: Gallbladder cancer (GBC) is relatively rare but has a high mortality rate. One candidate molecule which might be involved in GBC development is prostate stem cell antigen (PSCA), a glycosylphosphatidylinositol-anchored cell surface antigen with a tissue-specific pattern of expression in the epithelium of several organs, such as the prostate, stomach, bladder, and gallbladder. It is up-regulated in a number of cancers including prostate, urinary bladder, and pancreatic cancers, while it is down-regulated in eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 30 publications
2
69
0
Order By: Relevance
“…(35) The GBC cells introduced with PSCA cDNA showed lower in vitro and in vivo growth than controls, and their invasion ability assayed with a Matrigel chamber was also attenuated. (35) PSCA is expressed homogenously in normal gallbladder epithelium, which is characterized by a mono-layer of columner cells and functions by absorbing water and electrolytes. It is possible that PSCA has a role in cell-division control and/or other activities such as active transport of molecules in gallbladder epithelium.…”
Section: à6mentioning
confidence: 94%
See 4 more Smart Citations
“…(35) The GBC cells introduced with PSCA cDNA showed lower in vitro and in vivo growth than controls, and their invasion ability assayed with a Matrigel chamber was also attenuated. (35) PSCA is expressed homogenously in normal gallbladder epithelium, which is characterized by a mono-layer of columner cells and functions by absorbing water and electrolytes. It is possible that PSCA has a role in cell-division control and/or other activities such as active transport of molecules in gallbladder epithelium.…”
Section: à6mentioning
confidence: 94%
“…(37) The discrepancy between the in vitro reporter assay and the in vivo expression data further suggests a complexity of the PSCA regulation, which might be influenced by tissue-specific transcriptional factors and DNA methylation, as shown in gastric and gallbladder cancer cell lines. (35) In contrast, a recent study reported that the C allele of rs2294008 in PSCA was associated with an increased risk of duodenal ulcer (DU; odds ratio = 1.84; P = 3.92 9 10 À33 in a recessive model). (38) Moreover, the results of functional analyses showed that the C allele changes the subcellular localization of PSCA protein from the cell surface to the cytoplasm and also reduced the protein's stability.…”
Section: à6mentioning
confidence: 94%
See 3 more Smart Citations